Probit Models for Grouped-data Migration Flows: A Theoretical Note - Chasco, Coro; Aroca, Patricio; Anselin, Luc (Pontificia Universidad Católica del Perú. Fondo Editorial, 2019)
In this theoretical note, we propose the GProbit model as an alternative to gravity models to estimate grouped-data flows. This is a model based on the random utility theory, which is consistent with the principle of population behavior. Instead of migrant counts, the dependent variable of the GProbit model of flows consists of a number of observed proportions. It allows explaining the propensity to migrate from any origin to a destination, which is an interesting relative concept not affected by the size effect. For this reason, it is expected to have better fit and less problems of non-normality, as illustrated by an application for the internal migration flows of the Spanish regions.
Keywords: Probit model; Gravity model; Proportions; Migration flows; Spain; Migración; https://purl.org/pe-repo/ocde/ford#5.02.01